2016
DOI: 10.1590/s0004-28032016000400005
|View full text |Cite
|
Sign up to set email alerts
|

Early and Late Assessment of Esophagocardioplasty in the Surgical Treatment of Advanced Recurrent Megaesophagus

Abstract: Serra-Doria esophagocardioplasty for the treatment of advanced recurrent megaesophagus had mild postoperative complications and good success rate in the short-term follow-up. In the long-term follow-up, it proved to be a poor surgery choice because of the high incidence of symptom recurrence, compromising quality of life. This procedure should be indicated only for patients with advanced recurrent megaesophagus without clinical conditions to undergo esophageal resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…Neither treatment; however, seems to be ideal since they do not act directly on the physiopathology of the disease [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Neither treatment; however, seems to be ideal since they do not act directly on the physiopathology of the disease [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…O tratamento é sempre paliativo, seja ele clínico, endoscópico ou cirúrgico, pois não tem ação no fator etiológico da doença, tendo por objetivo somente o alívio sintomático e a profilaxia das complicações. As formas de tratamento incluem: medidas dietético-comportamentais; drogas que diminuam a pressão no esfíncter esofágico inferior, como bloqueadores do canal de cálcio, nitratos; procedimentos endoscópicos, como aplicação de toxina botulínica no esfíncter esofágico inferior, dilatação pneumática da cárdia e, mais recentemente, a miotomia endoscópica peroral; e o tratamento cirúrgico, como esofagocardiomiotomia e esofagectomia (TSUBOI et al, 2015;AQUINO et al, 2016).…”
Section: Tratamentounclassified
“…However, mid-term studies have shown that cardioplasties have not always yielded satisfactory results, mainly due to the difficulty in emptying the esophagus, and due to the gastroesophageal reflux that such procedure can trigger [20,[22][23][24]. This fact has been well demonstrated more recently by Aquino et al [25], who evaluated the 5 years late postoperative period in 19 patients with recurrent advanced achalasia who underwent SERRA DORIA cardioplasty and found that only 38.4% of the patients had normal swallowing and 53.8% of them had regurgitation, concluding that this procedure should only be indicated for patients without clinical conditions justifying esophagectomy.…”
Section: Introductionmentioning
confidence: 99%